# `(2c^2d)/(10c) -: (5d)/(3c^2)` I'm confused on this problem.

*print*Print*list*Cite

### 1 Answer

`(2c^2d)/(10c) -: (5d)/(3c^2)`

When we divide two fractions, the steps are:

> Flip the second fraction and change the operation from division to multiplication.

`=(2c^2d)/(10c) * (3c^2)/(5d)`

> Multiply the numerator of the first fraction with the numerator of the second fraction. Also, multiply the denominator of the first fraction with the denominator of the other.

`=(6c^2c^2d)/(50cd)`

> To multiply same variable, add the exponents ( `a^m*a^n=a^(m+n)` ).

`=(6c^(2+2)d)/(50cd)=(6c^4d)/(50cd)`

> To divide same variable, subtract the exponents (` a^m/a^n=a^(m-n)` ).

`=(6c^(4-1)d^(1-1))/50=(6c^3d^0)/50=(6c^3)/50`

Then, reduce the fraction 6/50 to its lowest term.

`=(3c^3)/25`

**Hence, `(2c^2d)/(10c)-:(5d)/(3c^2) = (3c^3)/25` .**

**Sources:**